Sensitivity Enhancement of an Inductively Coupled Local Detector Using a HEMT‐Based Current Amplifier. Issue 6 (20th July 2015) - Qian, Chunqi; Duan, Qi; Dodd, Steve; Koretsky, Alan; Murphy‐Boesch, Joe
Abstract : Purpose: To improve the signal transmission efficiency and sensitivity of a local detection coil that is weakly inductively coupled to a larger receive coil. Methods: The resonant detection coil is connected in parallel with the gate of a high electron mobility transistor (HEMT) transistor without impedance matching. When the drain of the transistor is capacitively shunted to ground, current amplification occurs in the resonator by feedback that transforms a capacitive impedance on the transistor's source to a negative resistance on its gate. Results: High resolution images were obtained from a mouse brain using a small, 11 mm diameter surface coil that was inductively coupled to a commercial, phased array chest coil. Although the power consumption of the amplifier was only 88 μW, 14 dB gain was obtained with excellent noise performance. Conclusion: An integrated current amplifier based on a HEMT can enhance the sensitivity of inductively coupled local detectors when weakly coupled. This amplifier enables efficient signal transmission between customized user coils and commercial clinical coils, without the need for a specialized signal interface.Magn Reson Med 75:2573–2578, 2016. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.